The 'new regionalism' and the Free Trade Area of the Americas : a less benevolent view - Bouzas, Roberto (2005)
Summarizes the main features of the 'new regionalism' and reviews some of the challenges and opportunities opened up by North-South preferential trade agreements. Underlines the importance of domestic policies to complement trade liberalization and the vital role these play when it comes to actually reaping the opportunities offered by the new regionalism. Reviews the FTAA negotiating to date, emphasizing recent trends and future prospects.